Criatividade e Consciência para o Século 21: Uma Poética da Alma - Soares, Paula (2008)
This paper aims at sharing some of the results of a PhD research in the area of Consciousness Studies, namely the presentation of a new model within a Poetics of the Soul concept. To start with, this paper will focus on a reflection on the Mission of Art (Goethe) and on the Creative Process based on selected testimonies of universally recognized artists. Further on, we will focus on the structure and location of the Levels of Consciousness as presented in the Huna Tradition, in Roberto Assagioli’s Psychosynthesis Model and in Ken Wilber’s Integral Psychology. As a result of the connection between the Mission of Art, the Levels of Consciousness and the Creative Process we will present a Poetics of the Soul model that aims at (re)integrating the Creator, the Mirror-work of Art and the Perceptor in a dynamic molecular structure as a means for the Creative Expression for the 21st Century.